ANALISIS ISI HOAX TENTANG VAKSIN COVID-19 DI KOMINFO.GO.ID - Mutiara Salma Amirah (2023)
Indonesia is one of the country that affected by the outbreak COVID-19. The outbreak of COVID-19 has affected Indonesia's public in many aspect. Until now there is no cure for this virus. Researchers are working hard to make a vaccine and find the best treatment for COVID-19 in reality. In this case, Indonesia not only fight against the pandemic but also battling with the widespread of fakenews in society. Knowing the fact that the widespread of fakenews can cause panic, disbelieve, and unease among Indonesia's public, the government and Ministry of Communication and Information Technology took steps to prevent this spread and working together to address hoaxes, misinformation, and disinformation. One of that through digital literacy. At the KOMINFO's website, people can also access on "Laporan Isu Hoaks", which allows them to type in and find the keyword to crosscheck the fact of the information that they're looking for, especially information or news that related to COVID-19. The fake news in this rubric 'Laporan Isu Hoaks" has been labelling by KOMINFO in to two categories; misinformation and disinformation so public can distinguish one news from another. In response, this study aimed to understand the tendency of misinformation and disinformation related to COVID-19, which has been fact-checked by KOMINDO in Maret 2020 - Februari 2021 period using quantitative content analysis using a coding scheme adapted from Irina Wolf. The results of the study found that based on the large number of hoax news spreads, 2021 was dominating and the topic category that was discussed the most was about vaccine safety factors. The dominance of the theme of hoax news and the year emphasized Indonesia's condition at that time, which still lacked information about the Covid-19 vaccine and was entering the second wave of Covid-19. Meanwhile, when viewed based on the category of hoax news writers, hoax news is widely spread by the authors directly using a lot of negative news atmosphere.